International Experience with Civil Service Censuses - Beschel, Robert; Mountfield, Edward (World Bank, Washington, DC, 2012)
Since the early 1980s many developing counties have tried to count and contain the number of civil servants as part of public sector reforms-including reforms funded by the World Bank. These initiatives, variously described as censuses, enumerations, headcounts, staff audits, payroll verifications, and payroll reconciliations, have been conducted in widely varying contexts, pursuing many different objectives and using a range of methodologies. But a recent survey by the World Bank and the International Records Management Trust shows that many such exercises have had limited success. How can these efforts be made more effective? Such censuses should have clearer objectives, use more appropriate methodologies, and pursue long-term improvements in payroll and personnel systems.